Thymoquinone-loaded lipid vesicles: a promising nanomedicine for psoriasis - Poonam Negi; Ishita Sharma; Chetna Hemrajani; Charul Rathore; Alpna Bisht; Kaisar Raza; O. P. Katare (BMC, 2019)
Abstract Background Psoriasis, a recurrent, chronic inflammatory disorder of skin, is a common problem in middle age and elderly people. Thymoquinone (TQ), a lipid soluble benzoquinone is the major active ingredient of volatile oil of Nigella sativa (NS), possesses good anti-psoriatic activity. However, its hydrophobicity, poor aqueous solubility, and photosensitive nature obstructs its development. Therefore, in the present research work, ethosomal vesicles (EVs) loaded with TQ were assessed for its anti-psoriatic potential employing mouse-tail model. Methods TQ-loaded EVs were prepared by cold method, and characterized for various essential attributes, viz. particle size, morphology, percent drug entrapment, flexibility, rheological and textural analysis, and skin absorption. The optimized formulation was finally evaluated for anti-psoriatic activity on Swiss albino mice employing mouse-tail model for psoriasis. Results The spherical shaped vesicles were in the nanosize range, and had high flexibility. The EVs incorporated hydrogel was rheologically acceptable and resulted in substantial TQ retention in the skin layers. The % anti-psoriatic drug activity was observed to be substantially better in the case of TQ-loaded ethosomal gel vis-à-vis plain TQ, NS extract, and marketed formulation. Conclusions The promising outcomes of the current studies ratify the superiority of TQ-loaded phospholipid-based vesicular systems for the management of psoriasis over other studied test formulations. This study, thus open promising avenues for topical application of TQ in the form of EV hydrogel.